Copper‐Catalyzed Chemo‐ and Enantioselective Radical 1,2‐Carbophosphonylation of Styrenes - Zhou, Huan; Fan, Li‐Wen; Ren, Yang‐Qing; Wang, Li‐Lei; Yang, Chang‐Jiang; Gu, Qiang‐Shuai; Li, Zhong‐Liang; Liu, Xin‐Yuan (Angewandte Chemie International Edition, 2023)
The copper‐catalyzed enantioselective radical difunctionalization of alkenes from readily available alkyl halides and organophosphorus reagents possessing a P−H bond provides an appealing approach for the synthesis of α‐chiral alkyl phosphorus compounds. The major challenge arises from the easy generation of a P‐centered radical from the P−H‐type reagent and its facile addition to the terminal side of alkenes, leading to reverse chemoselectivity. We herein disclose a radical 1,2‐carbophosphonylation of styrenes in a highly chemo‐ and enantioselective manner. The key to the success lies in not only the implementation of dialkyl phosphites with a strong bond dissociation energy to promote the desired chemoselectivity but also the utilization of an anionic chiral N,N,N‐ligand to forge the chiral C(sp3)−P bond. The developed Cu/N,N,N‐ligand catalyst has enriched our library of single‐electron transfer catalysts in the enantioselective radical transformations. Copper‐catalyzed chemo‐ and enantioselective radical 1,2‐carbophosphonylation of styrenes from readily available alkyl halides and dialkyl phosphites is developed. The key to the success of the strategy lies in not only the proper choice of phosphorus reagents to suppress the reverse chemoselectivity but also the utilization of a chiral N,N,N‐ligand to forge chiral C(sp3)−P bond.